Matching patterns in a group (public garden poems) By Saadi Youssef (Journal of the College of Basic Education, 2022)
Saadi Youssef has a distinguished case in the movement and modernity of poetry. It stands outDistinction in the details that monitor the contradictory and special psychological states and his abilityTo capture it and then transfer it to the recipient in multiple formats that meet and intersect to transmitThe poetic text is transformed into a pattern that suggests other hidden patterns that offer us new vocabularyWith her grandmother, she formed various types of collocations, such as lexical, spatial, and kinesthetic collocationsand others. These are encounters that prove to us that it is the language that makes the encounter with its existenceWithin the totality of dissonant speech phenomena, and in order to clarify this, a study must be madeRelationships between vocabulary within the contrasting field and comparing them with their sub-topic.This is what we will try to prove in this research.